0(3Sdhc GdeSJgdc (B:s (3eONd GdGYdGf (B/s - (3GdefUhQ, cGSQ fUQs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ h GdJhRjY(B, s, 2006)
(3GdJShjb h Sdhc GdeSJgdc h JLRFI GdShb h eaghe GdSdhc GdEfSGfj h YedjI GJNGP GdbQGQ GdTQGFj ceG Je JfGhd MGLGJ GdeSJgdc h OhGaYg h GdTNUjI h Sdhc GdeSJgdc h cPG EOQGc GdeSJgdc h GdJYde h Sdhc GdeSJgdc ceG Je GdJWQb Gdi GdKbGaI h Sdhc GdeSJgdc h cPG GdWHbI GdGLJeGYjI h Sdhc GdeSJgdc h GdCSQI h Sdhc GdeSJgdc h GdLeGYGJ GdeQLYjI h Sdhc GdeSJgdc h cPG GdGJUGdGJ h Sdhc GdeSJgdc h GdGHJcGQGJ GdSdYjI h YedjI JHfj GdSdYI h Gdehba GdTQGFj h Sdhc GdeSJgdc (B.s
(3eQGLY U(B.314s
Keywords: (3GdGYdGfs; (3GdJShjbs